Concentration of biopetrol from palmitic acid - Noor Zariyati, Mohammad (2008)
Biopetrol is defined as fuel which has the same characteristics with commercial petrol in terms of its molecular formula. The objective of this study is to find the concentration of biopetrol (isooctane) from palmitic acid. Thermal cracking process is used to produce isooctane from palmitic acid. Heat is supplied using hot plate at palmitic acid’s melting point within a range of 63oC – 64oC, to melt the solid palmitic acid. After it turns to liquid, the heating is continuous at isooctane’s boiling point of 98oC by using heating mantel 250ml to form new arrangements of carbon compounds including isooctane. The heating is continuous and the sample was collected at temperature 200oC, 300oC, 330oC and 350oC. The desired isooctane obtained is around 0.0455% - 0.0743% in the distilled palmitic acid. After the back calculation, the highest concentration of the desired isooctane is 2.92% at temperature 350oC palmitic acid.